Methylenetetrahydrofolate Reductase Gene C677T and A1298C Polymorphic Sequence Variations Influences the Susceptibility to Chronic Myeloid Leukemia in Kashmiri Population - Baba, Shahid M.; Shah, Zafar A.; Javaid, Khushboo; Pandith, Arshad A.; Rasool, Javeed; Geelani, Sajad A.; Baba, Rafia A.; Amin, Shajrul; Mohammad, Gul (Frontiers in Oncology, 2019)
Background Methylenetetrahydrofolate reductase (MTHFR) gene is a crucial regulator of folate metabolism and its two prominent polymorphic variants C677T and A1298C lead to decreased MTHFR enzyme activity. Aim of the study We planned this case–control study based on numerous studies supporting the association of MTHFR polymorphisms (C677T and A1298C) with CML risk in different ethnic populations. Therefore, the influence of these polymorphisms on CML susceptibility among Kashmiri population (North India) was investigated. Material & Methods Polymerase chain reaction/restriction fragment length polymorphism technique was employed for genotyping MTHFR C677T and A1298C SNP’s in 125 CML patients as against 150 age and gender matched healthy controls. Results A significant difference was observed in frequency of 677CT genotype between cases and controls [46.4% vs 27.3% (p=0.0005)]. Similarly combined 677CT+TT genotype showed significant difference between cases and controls [50.4% vs 28.6% (p=0.0002)]. Both MTHFR 677CT and 677CT+TT genotypes imposed greater than 2 fold risk of developing CML (OR=2.4, 95%CI: 1.46-4.05; OR=2.5, 95%CI: 1.53-4.16). In case of A1298C SNP, the frequency of 1298AC genotype was higher in controls (64.0%) as compared to CML cases (48.8%) (p=0.04) and imparted a significant protective role from CML predisposition. Furthermore, haplotype analysis revealed only ‘677CT/1298AA’ haplotype significantly increased the risk of CML predisposition [(p=0.008) (OR = 3.2, 95% CI: 1.3-7.4)]. Conclusion We conclude that both MTHFR C677T and A1298C polymorphisms act as important genetic modifiers for CML risk in Kashmiri population, where C677T SNP strongly increases the risk of CML while as A1298C SNP has a protective effect.